Does spatial performance improve by practice effects? - Contreras, María José; Martínez-Molina, Agustín; Manzanero, Antonio; Peña, Daniel; Santacreu, José (Anales de Psicología / Annals of Psychology, 2009)
Can the abilities be learning? Although there is some consensus that abilities are developed, there is little consensus on how this develop-ment might occur (Lohman & Nichols, 1990). One approach in spatial ability has been the study of feedback and practice effects. The aim of the present study was to analyse these effects on dynamic spatial ability. 42 subjects completed two dynamic tasks (SODT-R and SDT 2.0) during the first experiment. Both tasks consisted of to guide two moving dots toward a destination, manipulating three levels of traces (feedback) and the number of trials (practice; 9 vs.18). In the second experiment, 52 subjects did the same task with SDT 2.0 procedure, also manipulating three levels of traces and the number of trials (12 vs. 24 vs. 36). Data showed level of traces and practice influenced dynamic spatial ability. Subject’s performance was better when more feedback traces were given and when more trials were done. We discuss theoretical implications based on the human learning and capacity processes.